PATOGENESITAS Spodoptera exigua NUCLEO POLYHEDRO VIRUS UNTUK MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera exigua Hubn) DI PERTANAMAN BAWANG MERAH (Allium ascalonicum) SECARA IN VITRO - Dewi Hastuti; Andree Syailendra; Nur Iman Muztahidin (Jurnal Agroekoteknologi, 2016)
Control of Grayak Caterpillar (Spodoptera exigua Hubn) pest by farmers generally is still use synthetic insecticides that have such a negative impact resistance, resurgence, killing natural enemies, increasing residue on crop yields, environmental pollution and health problems for users. One effort to reduce the use of chemical insecticides namely biological control method uses the Spodoptera exigua Nucleo Polyhedro Virus. This research was aimed to know the mortality rate army worm (Spodoptera exigua Hubn) by suspension Spodoptera exigua Nucleo Polyhedro Virus with different concentration. This research was conducted in the laboratory and green house of Vegetable Crops Research Institute at Lembang, Bandung from July until September 2014. This research used Randomized Completely Design (RCD). The result showed that Spodoptera exigua Nucleo Polyhedro Virus was significant to death of Spodoptera exigua. Spodoptera exigua Nucleo Polyhedro Virus concentration showed significant to mortality rates of Spodoptera exigua. In the test stage, the larvae of Spodoptera exigua 2 was the highest stage mortality was caused by infection Spodoptera exigua Nucleo Polyhedro Virus. Method of dipping caterpillars and feed applications were the best treatment because it showed the highest mortality. Pest control Grayak Caterpillar (Spodoptera exigua) in the field could use Spodoptera exigua Nucleo Polyhedro Virus coarse suspension of 10 g L-1 which was applied to the onion crop that was attacked.Keywords: Spodoptera exigua, Spodoptera exigua Nucleo Polyhedro Virus, Onion